THE LEVEL OF MEDICATION ADHERENCE IN HYPERTENSIVE PATIENTS: Gambaran Kepetuhan Minum Obat pada Penderita Hipertensi - Agung Nugroho, Fajar (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
Background: Hypertension (high blood pressure) is when the pressure in your blood vessels is too high (140/90 mmHg or higher). It is common but can be serious if not treated. A patient with hypertension who receives a treatment, implements a diet program, and carries out activities must comply with the recommendations of health workers. Objective: To find out the level of medication adherence in hypertensive patients at Selokerto Village. Method: This study was a quntitative study with a cross-sectional approach. The research sample was 100 people with hypertension at Selokerto Village and they were taken by total sampling method. Result: The results of this study were 63 (63%) respondents with a high level of medication adherence and 37 (37%) respondents with a moderate level of medication adherence. Conclusion: The level of medication adherence in Selokerto Village was dominantly good medication adherence. Recommendation: For further research, researchers are expected to examine the factors associated with medication adherence.